The outcomes and experience of pregnancy in limb girdle muscular dystrophy type R9. Issue 6 (10th February 2021) - Libell, Eric M.; Bowdler, Noelle C.; Stephan, Carrie M.; Zimmerman, Miriam Bridget; Gedlinske, Amber M.; Mathews, Katherine D.
Abstract: Introduction: Published information about the experiences of pregnancy in limb girdle muscular dystrophy (LGMD) is limited and does not specify LGMD type, limiting utility. We describe the experience and outcomes of pregnancy in a cohort of women with LGMD type R9 (LGMDR. Methods: All women 18 y of age or older with a genetic and clinical diagnosis of LGMDR9 who are enrolled in the University of Iowa Wellstone dystroglycanopathy natural history study (clinicaltrials.gov NCT00313677) were invited to complete a questionnaire about their pregnancy experiences, including questions about pregnancy complications, muscle symptoms experienced during pregnancy, and post‐partum course. Results: A total of 22 women responded to the survey. Thirteen women reported 26 live births. The majority of pregnancies that resulted in a live birth were uncomplicated (n = 19, 73%), and most infants had no complications (n = 25, 96%). The rates of assisted vaginal delivery (n = 9, 35%) and induction of labor (n = 18, 70%) were both significantly higher than the national average. Almost half of pregnancies (n = 11, 42%) resulted in increased weakness during pregnancy; only one returned to pre‐pregnancy baseline. Discussion: The data presented here suggest that women with LGMDR9 who are considering a pregnancy should be counseled that they might have a higher likelihood of assisted vaginal delivery and could experience progression of weakness. These results are generally consistent with previous reports, but future studies of pregnancy in defined subtypes of LGMD will be required to confirm these findings and determine if risks vary by genotype. Abstract : See Editorial on pages 787–789 in this issue .